How Barack Obama is endangering our national sovereignty - Bolton, John R. (Encounter broadsides, 2010)
American sovereignty is today more challenged than ever before, not from enemies that threaten us militarily but from "friends" who urge that we share or reduce our sovereignty for larger global objectives. How Barack Obama is Endangering our National Sovereignty reveals what sovereignty means to Americans, not as an abstraction but a vibrant component of self government, what the threats are to that sovereignty from "global governance," and how President Barack Obama looks at these issues. Former Ambassador to the U.N. John R. Bolton looks at specific threats to U.S. sovereignty and.